Facile treatment tuning the morphology of Pb with state-of-the-art selectivity in CO2 electroreduction to formate. Issue 60 (6th July 2021) - Yu, Weiting; Wen, Lingsha; Gao, Jie; Chen, Sizhuo; He, Zhiqiao; Wang, Da; Shen, Yi; Song, Shuang
Abstract : The highest selectivity of the CO2 RR toward formate reported to date has been achieved on well-defined octahedral Pb prepared via a facile treatment on commercial Pb. Abstract : This study presents a facile treatment to modify the commercial irregular shaped polycrystalline Pb into well-defined octahedral Pb with unique Pb(111) facets. Efficient, selective, and stable electrochemical reduction of CO2 toward formate has been achieved on the treated Pb electrode. The faradaic efficiency of formate production from the CO2 RR is 98.03%, which is the highest reported to date. The results from the combination of theoretical calculations and experimental tests demonstrate that the enhanced catalytic performance on the treated Pb electrode stems from the electrode morphology characterized by a unique Pb(111) surface with lower Gibbs free energies (Δ G ) for the formation of intermediate OCHO*.